2018
DOI: 10.7556/jaoa.2018.060
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Tests and X-ray Imaging in a Surgical Intensive Care Unit: Checking the Checklist

Abstract: The addition of the diagnostic testing section to the daily checklist did not result in a reduction of the amount of tests ordered per day. Further research on test appropriateness and the possible addition of a clinician decision-making tool could be studied in the future to assist with reduction of tests ordered in the surgical ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…We included a total of 81 records representing 70 studies: 50 nonrandomized interventional studies (19–68) and 20 observational studies (69–88) ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included a total of 81 records representing 70 studies: 50 nonrandomized interventional studies (19–68) and 20 observational studies (69–88) ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five out of 70 studies (36%) reported frequencies of all routine blood tests measured as tests per patient day (20, 23–25, 29, 33, 34, 36–38, 46, 48, 50, 52, 53, 59, 62, 64, 68, 75–78, 80, 88).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The database search yielded a total of 3362 results, from which a total of 28 studies were included in the qualitative synthesis (Fig. 1) [3, 5, 9, 12–14, 21, 26–46].…”
Section: Resultsmentioning
confidence: 99%
“…All studies demonstrated significant improvements in most criteria, such as the documentation of date and time, clinician leading ward round, impression, management plan, and venous thromboembolism (VTE) assessment. Alamri and colleagues [28] reviewed compliance against a proforma sticker utilised in a previous study [27] Resources and personnel Yorkgitis et al [46] introduced a laboratory tests and chest X-ray imaging section on their daily intensive care unit (ICU) checklist. There was no significant difference in the mean number of chest x-rays and coagulation tests requested each day.…”
Section: Documentation Criteriamentioning
confidence: 99%